2017
DOI: 10.23855/preslia.2017.017
|View full text |Cite
|
Sign up to set email alerts
|

Ecological hybrid speciation in central-European species of Bolboschoenus

Abstract: Divergent natural selection is known to facilitate speciation in many taxa. The genus Bolboschoenus (Cyperaceae) is a model group for investigating ecological and homoploid hybrid speciation. Four taxa of Bolboschoenus occur in central Europe: the halophyte B. maritimus and glycophytes B. laticarpus, B. planiculmis and B. yagara. These species differ in their ecological niches. Such ecological and/or geographical isolation is critical for homoploid hybrid speciation. The determination of species of Bolboschoen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…In addition, the parental species were well recognized even in a robust dataset containing 13 different species. The applicability of this technique for studying hybridization events was demonstrated recently by Čertner et al (2015), Hulber et al (2015), Szczepaniak et al (2016), Zelener et al (2016), An et al (2017), Píšová et al (2017) and others. In the genus Cirsium it was also used for the molecular confirmation of a new hybrid by Segarra-Moragues et al (2007).…”
Section: Genetic Analysesmentioning
confidence: 78%
“…In addition, the parental species were well recognized even in a robust dataset containing 13 different species. The applicability of this technique for studying hybridization events was demonstrated recently by Čertner et al (2015), Hulber et al (2015), Szczepaniak et al (2016), Zelener et al (2016), An et al (2017), Píšová et al (2017) and others. In the genus Cirsium it was also used for the molecular confirmation of a new hybrid by Segarra-Moragues et al (2007).…”
Section: Genetic Analysesmentioning
confidence: 78%
“…(= B. planiculmis (F. Schmidt) T. V. Egorova). Detailed molecular studies by Píšová et al (2017) have demonstrated this to be the case: B. laticarpus is genetically and morphologically intermediate between B. yagara and B. planiculmis and is a stable hybridogenous species.…”
Section: Introductionmentioning
confidence: 95%
“…Plants of genus Bolboschoenus are commonly distributed in saline wetlands, and often occupy a wide range of habitats, including both coastal and inland salt marshes (Ljevnaić-Mašić et al, 2020). The ecological properties of these species such as their dispersal abilities and distribution as well as their relationships with habitat conditions, have been are investigated (Hroudová et al, 2007;Píšová et al, 2017). Bolboschoenus maritimus, for example, is regarded as a halophyte usually inhabiting saline habitats.…”
Section: Introductionmentioning
confidence: 99%